A quantitative risk assessment development using risk indicators for predicting economic damages in construction sites of South Korea. Issue 5 (3rd September 2019) - Kim, Ji-Myong; Kim, Taehui; Son, Kiyoung; Bae, Junseo; Son, Seunghyun
ABSTRACT: The purpose of this study is to suggest a quantitative risk assessment approach for construction sites using risk indicators to predict economic damages. The frequency of damage in building construction has recently increased, and the associated costs have been increased as well. Although a request for a damage estimation model has been extended, the industry still lacks quantitative and comprehensive research that reveals the physical relationship between damage and risk indicators. To address that issue, we use an insurance company's payouts from construction site claims in South Korea to reflect the real financial damage. We adopted a multiple regression method to define the risk indicators: geographic vulnerability, natural hazards, capability, and general project information. The results and findings of this research will be accepted as an essential guideline for developing a construction risk estimation model.